Ecomuseu da Amazônia: um repensar sobre a prática museológica - SOUZA, Regina Lucia Tavares Lôbo de (2019)
This research has as reference the Ecomuseum of the Amazon. This museological institution presents a proposal of work that involves the communities within its scope of action, to know: Mosqueiro Island, Caratateua Island (Outeiro), Icoaraci and Island of Cotijuba, aiming to strengthing of their cultural practices and the development of the people that are inserted in this context. Considering that the Island of Cotijuba is an integral part of the field of activity of the Ecomuseum, this work deals in particular with the narratives of the social groups of residents and visitors of the Island of Cotijuba, who demonstrate the notions related to the museum and patrimony from them, among other issues presented in field research. Taking as reference that the ecomuseus are configured as a new modality of museum, that emerged with the advent of New Museology, a theoretical current that proposes to rethink the usual museological practices, in the sense of allowing a greater interaction between the museum and people, aiming his development. Thus, this paper presents the result of the qualitative research that involved the application of interviews between groups of residents and visitors of the Island. Analyzing their perceptions and experiences about possible museological actions in the region, it is believed that the ecomuseum needs to establish a more comprehensive dialogic approach with the communities around the Island, in order to establish an interactivity relationship between this museum and these communities.